(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
This excellent text, recently published in the Policy Press Rethinking Community Development series, critically explores the relationship between arts, culture and community development in different parts of the globe including Lebanon, Latin America, China, Ireland, Sri Lanka, Chile, Brazil, and Finland. Arts and culture in this book are taken as being created in a manner that is participatory and practised by those involved as equals. This recognises that people bring different skills and talents, and all should be understood as being part of a democratic enterprise.